2019
DOI: 10.1002/jbio.201960063
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of intrinsic skin aging between Caucasian and Asian subjects by slide‐free in vivo harmonic generation microscopy

Abstract: Phenotypical and functional differences in the intrinsic skin aging process of individuals between Caucasians and Asians have generated considerable interest in dermatology and cosmetic industry. Most of the studies focused on the stratum corneum, and in some other studies inter-individual differences overwhelms the racial difference. None of the studies comparatively analyzes the difference from the histopathological point of view. Here we report our harmonic generation microscopy study to analyze the differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
17
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 33 publications
4
17
1
Order By: Relevance
“…Extensive studies and discussions have been conducted and previously published to address this concern, especially for the 1230-1260 nm based femtosecond THG microscopy with an average power on the order of 100 mW [22,34,[46][47][48][49][50]. No evidence of photodamage can be found either in clinical trials [22,32,34,35,[51][52][53][54][55] or studies on animal models [22,[47][48][49][50]. This is attributed to the low photon energy (∼1eV) of the adopted excitation light, which avoids the linear melanin absorption [22] and significantly increases the multi-photon ionization threshold [34], when compared with femtosecond excitation light with a higher photon energy.…”
Section: Photodamage and Laser Induced Measurement Biasmentioning
confidence: 99%
“…Extensive studies and discussions have been conducted and previously published to address this concern, especially for the 1230-1260 nm based femtosecond THG microscopy with an average power on the order of 100 mW [22,34,[46][47][48][49][50]. No evidence of photodamage can be found either in clinical trials [22,32,34,35,[51][52][53][54][55] or studies on animal models [22,[47][48][49][50]. This is attributed to the low photon energy (∼1eV) of the adopted excitation light, which avoids the linear melanin absorption [22] and significantly increases the multi-photon ionization threshold [34], when compared with femtosecond excitation light with a higher photon energy.…”
Section: Photodamage and Laser Induced Measurement Biasmentioning
confidence: 99%
“…With the same mechanism, absolute quantities of melanin of keratinocytes in human skin can be noninvasively measured by using third harmonic generation enhancementratio microscopy [15]. Combining THG with second harmonic generation (SHG) microscopy, Liao et al pointed out that some structural variables, including the thickness of dermal papilla zone (DPZ) [16,17] and the size of keratinocytes [17,18], have a statistically significant relationship with intrinsic skin aging. Similarly, Kapsokalyvas et al used in vivo SHG microscopy to measure and characterize the dermal papilla length, corresponding to DPZ thickness, in psoriatic and healthy skin as well [19].…”
mentioning
confidence: 99%
“…With a laser repetition rate of 105 MHz, the corresponding pulse energy was 0.95 nJ per pulse, with a maximum pulse fluence of 0.18 J/cm 2 at the focal spot and a corresponding scanning power density of 181 W/cm 2 at the sample plane. Under the same experimental conditions, pervious clinical studies indicated that the nonlinear photodamage for 1260-nm is far below the threshold to cause the DNA damage and can be negligible [42][43][44][45][46][47][48]54 . After HGM imaging of the same imaging condition, previous in vivo clinical studies reported that there was no erythema, pigmentation, crust, or vesicular formation, nor does the volunteer feels heat or discomfort [42][43][44][45][46][47][48]54 .…”
Section: Case Number Groupmentioning
confidence: 91%
“…In this article, we report our OC study on ex vivo human skin with 50% glycerol application by harmonic generation microscopy (HGM). By adopting a femtosecond excitation light 40 located at the skin penetration window around 1300 nm 41 , HGM has been confirmed to be a noninvasive histopathology imaging tool for the differential diagnosis of various skin lesions [42][43][44][45][46] , the study of skin aging 10,47,48 , and other clinical tissues [49][50][51][52] . For comparison purpose, we applied 100% or 50% glycerol by immersion or topical application on human skin to observe if the OC effect varied.…”
Section: Investigating the Optical Clearing Effects Of 50% Glycerol Imentioning
confidence: 99%
See 1 more Smart Citation